Routine detection of Clostridium difficile in Western Australia. (February 2016) - Collins, Deirdre A.; Riley, Thomas V.
Abstract: Despite increasing infection rates, Clostridium difficile is not currently routinely tested for in all diarrhoeal faecal specimens in Australia. In July 2014, all diarrhoeal specimens submitted to a diagnostic laboratory in Western Australia were surveyed to determine the true prevalence of C . difficile . In total, 1010 diarrhoeal non-duplicate faecal specimens were received during the month. Testing for C . difficile was requested, or the criteria for a C . difficile investigation were met, for 678 specimens which were investigated by PCR for the tcdB gene using the BD MAX platform, followed by toxigenic culture on PCR-positive samples. The remaining 332 specimens, with either no C . difficile test request or the criteria for a C . difficile investigation were not met, were examined by toxigenic culture. All isolates were PCR ribotyped. C . difficile was the most commonly detected diarrhoeal pathogen among all specimens. The overall prevalence of C . difficile in all 1010 specimens was 6.4%; 7.2% in the routinely tested group, and 4.8% in the non-requested group. The proportion of non-requested positive detections among all cases was 24.6%. Community-onset infection was present in 50.8% of all cases. The median age of all CDI cases was 60.0 years and the age range in CDI patients in the routine group was 0.6–96.6 years (median 72.7 years), compared to 0.2–2.3 years (median 0.8 years) in the non-requested group. The most common ribotype (RT) found was RT 014/020 (34.1% in the routine group, 43.8% in the non-requested group), followed by RTs 002, 056, 005 and 018. While the routine testing group and the non-requested group differed markedly in age and patient classification, C . difficile was the most common cause of diarrhoea in hospitals and the community in Western Australia. The significance of finding C . difficile in the community paediatric population requires further study. Highlights: A survey of all diarrhoeal specimens over 1 month in a Western Australian diagnostic laboratory was performed. Clostridium difficile was identified in 6.4% of all 1010 specimens. 24.6% of cases were missed by routine testing. 50.8% of cases were community-onset infection.